Mengajarkan Bahasa Arab kepada Anak-Anak Usia Dini dengan Aplikasi Arabic Vocabulary for Kids - Iva Setyawati; Laili Mas Ulliyah Hasan (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This research uses a qualitative approach with a case study design to explore the use of the "Arabic Vocabulary for Kids" application in learning Arabic for young children. Participants in this study consisted of 10 children aged 4-6 years, as well as their parents and teachers. Data was collected through observation, in-depth interviews and documentation for four weeks. Observations were conducted to monitor children's interactions and engagement with the app, while semi-structured interviews with parents, teachers and children were used to explore their perceptions of the app. Documentation in the form of screenshots and audio/video recordings was also collected to support the findings. Data analysis was carried out using the thematic analysis method, which involves data transcription, coding, theme development, and interpretation. The validity and reliability of the research were maintained through source triangulation, member checking, and peer debriefing. Ethical aspects of the research were maintained by obtaining written consent from parents and teachers, maintaining confidentiality of participants' identities, and ensuring the welfare of children during the research process. The research results show that the "Arabic Vocabulary for Kids" application is effective in increasing children's interest and involvement in learning Arabic. These findings provide in-depth insight into the effectiveness of apps in Arabic language learning and suggest recommendations for app developers, educators, and parents to improve children's learning experiences.